A metabolomic approach to identify the link between sports activity and atheroprotection. (12th December 2020) - Beutner, Frank; Ritter, Christian; Scholz, Markus; Teren, Andrej; Holdt, Lesca Miriam; Teupser, Daniel; Becker, Susen; Thiele, Holger; Gielen, Stephan; Thiery, Joachim; Ceglarek, Uta
Abstract: Aims: Physical activity (PA) is a mainstay of cardiovascular prevention. This study aimed to identify metabolic mediators of PA that protect against the development of atherosclerosis. Methods and results: A total of 2160 participants in the LIFE heart study were analysed with data on PA and vascular phenotyping. In a targeted metabolomic approach, 61 metabolites (amino acids and acylcarnitines) were measured using liquid chromatography–tandem mass spectrometry. We investigated the interactions between PA, metabolites and markers of atherosclerosis in order to uncover possible mediation effects. Intended sports activity, but no daily PA, was associated with a lower degree of atherosclerosis, odds ratio (OR) for total atherosclerotic burden of 0.76 (95% confidence interval 0.62–0.94), carotid artery plaque OR 0.79 (0.66–0.96), and peripheral artery disease OR 0.74 (0.56–0.98). Twelve amino acids, free carnitine, five acylcarnitines were associated with sports activity. Of these, eight metabolites were also associated with the degree of atherosclerosis. In the mediation analyses, a cluster of amino acids (arginine, glutamine, pipecolic acid, taurine) were considered as possible mediators of atheroprotection. In contrast, a group of members of the carnitine metabolism (free carnitine, acetyl carnitine, octadecenoyl carnitine) were associated with inactivity and higher atherosclerotic burden. Conclusion: Our metabolomic approach, which is integrated into a mediation model, provides transformative insights into the complex metabolic processes involved in atheroprotection. Metabolites with antioxidant and endothelial active properties are believed to be possible mediators of atheroprotection. The metabolomic mediation approach can support the understanding of complex diseases in order to identify targets for prevention and therapy.